Kekerabatan: Keunggulan Strategi Dakwah Wali Sanga - Sukarma, Sukarma (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2023)
The spread of Islam to the archipelago was first carried out using various methods and channels; trade, political power, art, and so on. However, the first generation of missionary pioneers in Java, who were popularly known as Wali Sanga, chose to utilize the medium of kinship ties that genealogically connected fellow practitioners of the mission, and between them and strategic community groups who were the objects of Islam. In reality, such a transformation model has proven effective in increasing the success of Islamic penetration, and the Wali-wali are increasingly recognized for their role in the community structure of the indigenous population. Even then, through these signs of continuity of descent, society's conversion to Islam shifted from its initial state of just individual action to a massive phenomenon when this religion was widely accepted by the majority of the population, which is now the largest concentration in the world. Keywords: Islam Nusantara, cultural, kindship, Wali Sanga